PERBANDINGAN TINGKAT KELENGKAPAN MANDATORY DISCLOSURE DAN VOLUNTARY DISCLOSURE INFORMASI AKUNTANSI (Studi empiris pada Perusahaan BUMN dan BUMS yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Salma Kholis Arjunawati; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this research is actually to find out clearly whether companies that have been managed and owned by the state, namely BUMN companies, have actually made disclosures of financial reporting that have been determined and authorized by Bapepam or are still lacking in making disclosures both compulsorily and voluntarily and as researchers compared the comparison to BUMS companies. Through  the calculation  of the index value of the completeness of the level of disclosure whose analysis results are used as a comparison using the t test (Independent Sample t-Test), where the results of the study indicate that the significance value (2-tailed) 0.000 < 0.05 which means H1 is accepted so it can be concluded that there are significant differences in  the level of completeness of mandatory disclosure of accounting information between BUMN and BUMS companies. then shows the significance value (2-tailed) 0.549 > 0.05 which means H2 is rejected so it can be concluded that there is no significant difference in the level of voluntary disclosure of accounting information between BUMN and BUMS companies. Keywords: Level of Completeness, Mandatory Disclosure, Voluntary Disclosure, BUMN, BUMS, Accounting Information.